Temporary Immersion Culture: A Potential In Vitro Culture Method for the Clonal Propagation of Coconut - Zhihua Mu; Zhiying Li; Amirhossein Bazrafshan; Sundaravelpandian Kalaipandian; Eveline Yee Yan Kong; Julianne Biddle; Naga Prafulla Chandrika Nulu; Steve Adkins (Horticulturae, 2024)
As one of the most important members of the palm family, coconut (Cocos nucifera L.) currently faces a substantial gap between demand and production. Current plantings of this crop are aging, and these traditional varieties are susceptible to several devastating pests and diseases. Consequently, there is an urgent need to replant and expand coconut lands with new, genetically superior varieties. Such replanting cannot be met through the conventional method of seed nut planting, and tissue culture has emerged as a likely solution to address this problem. However, due to certain technical barriers, elevated costs, and a need for improved efficiency, the development of automated and highly efficient tissue culture techniques is yet to be developed. The present research explores the potential of an in vitro temporary immersion system (TIS) to improve the production of somatic embryogenic callus for plantlet regeneration. Results indicated that, in comparison to the conventional agar-based method used to produce coconut somatic embryogenic callus, the TIS method significantly enhanced embryogenic callus production. The optimal biomass of callus for inoculating the TIS was determined to be 0.2 g in each 900 mL vessel and the most favorable embryogenic developmental stage for employing TIS was the globular stage of embryo development. The most effective immersion time to give the highest yield of embryogenic callus was 5 min every 6 h. This foundational research demonstrates that a TIS step is likely to be important to rapidly produce, on a large scale, coconut plantlets to meet the escalating demand for materials for the replanting of coconut lands.